Navigating the Silent Struggle: A Narrative Inquiry into EFL Teachers’ Problem-Focused Coping Strategies for Slow Learners - Rodiatul Audiyah Lubis; Farida Repelita Waty Br. Kembaren (Universitas Islam Negeri Palopo, 2026)
This study explores how EFL teachers apply problem-focused coping (PFC) strategies, such as instructional adaptation, material modification, and remedial support, when teaching slow learners in inclusive classrooms. The study addresses a gap in the literature by examining teachers’ coping strategies within the context of Indonesian inclusive EFL classrooms, an area that remains underexplored. Using a narrative inquiry approach, the study involved two female EFL teachers from a private inclusive school in Medan, Indonesia, selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews focusing on teachers’ professional experiences in managing heterogeneous classrooms. The data were analyzed using thematic analysis based on Braun and Clarke’s framework. The findings reveal that teachers actively adjusted instructional practices, modified learning materials, and implemented remedial activities to address slow learners’ cognitive challenges. These strategies not only enhanced students’ classroom engagement but also helped reduce teachers’ emotional burden. The study highlights the importance of strengthening inclusive education training for EFL teachers to support the effective implementation of active coping strategies in diverse classroom settings.